2021
DOI: 10.1186/s43094-021-00346-9
|View full text |Cite
|
Sign up to set email alerts
|

Receptor tyrosine kinases as a therapeutic target by natural compounds in cancer treatment

Abstract: Background Receptor tyrosine kinases (RTKs) are single-pass transmembrane proteins that play significant roles in regulating cellular processes, including cell division and growth. Overexpression and mutations of RTKs have been found in clinical manifestations of different forms of cancer. Therefore, RTKs have received considerable interest as a therapeutic biomarker in the treatment of cancer cells. Main body of the abstract Comprehensive data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 118 publications
0
9
0
Order By: Relevance
“…Comparing the EGFR TK inhibitory activity of the new indole derivatives (3 a-3 f) incorporating thiosemicarbazide moiety to their corresponding compounds incorporating triazole moiety (4 a-4 c) and oxadiazole moiety (5), indicated that the thiosemicarbazide moiety is more advantageous than the triazole and oxadiazole moieties (Figure 2A). Regarding compounds containing thiosemicarbazide linkers (3 a-3 f), introduction of a methoxy group at p-position (compound 3 f) exhibited lower activity than methyl in p-position (compound 3 c) (Figure 2B), while replacement of the bromo group in the p-position (compound 3 e) with another electronegative substituent as the pchloro group or nitro group (compounds 3 d and 3 b) increases the activity (Figure 2C).…”
Section: Structure-activity Relationships (Sar)mentioning
confidence: 99%
See 4 more Smart Citations
“…Comparing the EGFR TK inhibitory activity of the new indole derivatives (3 a-3 f) incorporating thiosemicarbazide moiety to their corresponding compounds incorporating triazole moiety (4 a-4 c) and oxadiazole moiety (5), indicated that the thiosemicarbazide moiety is more advantageous than the triazole and oxadiazole moieties (Figure 2A). Regarding compounds containing thiosemicarbazide linkers (3 a-3 f), introduction of a methoxy group at p-position (compound 3 f) exhibited lower activity than methyl in p-position (compound 3 c) (Figure 2B), while replacement of the bromo group in the p-position (compound 3 e) with another electronegative substituent as the pchloro group or nitro group (compounds 3 d and 3 b) increases the activity (Figure 2C).…”
Section: Structure-activity Relationships (Sar)mentioning
confidence: 99%
“…Receptor tyrosine kinases (RTKs) get activated when a growth factor binds to their extracellular domain and induces dimerization of the receptors. [5] RTKs belonging to the epidermal growth factor receptor (EGFR) family are crucial for controlling cell migration, survival, proliferation, and differentiation. On the other hand, the vascular endothelial growth factor receptor (VEGFR), another RTK, is a crucial component of signal transduction pathways involved in angiogenesis and neovascularization.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations